Thermal and mechanical properties of polypropylene nanocomposites reinforced with nano-SiO2 functionalized graphene oxide. (June 2017) - Bian, Jun; Wang, Zheng Jun; Lin, Hai Lan; Zhou, Xing; Xiao, Wen Qiang; Zhao, Xin Wei
Abstract: In this paper, a novel PP nanocomposites containing graphene/SiO2 hybrid (GOS) was fabricated via melt blending. It showed that GO has been chemically functionalized by selective monomers. Due to the existence of "heterogeneous nucleation effect", the melting temperatures and thermal properties were improved, as verified by thermal analysis. GOS has been dispersed uniformly in the PP matrix due to the "barrier effects" between SiO2 and graphene sheets. Tensile tests showed that GOS filler provided substantially greater mechanical property enhancement when embedded into PP matrix. When the GOS filler loading was 0.25 wt.%, the tensile and impact strength of PP nanocomposite increased by 13.8% and 41% compared with those of pure PP and by 27.95% and 43.87% respectively, compared with those of PP nanocomposites that filled with GO alone, indicating that the combination of graphene and nano-SiO2 demonstrated a synergistic effect for the property enhancement of PP.